2021
DOI: 10.5093/jwop2021a7
|View full text |Cite
|
Sign up to set email alerts
|

Faking Effects on the Factor Structure of a Quasi-Ipsative Forced-Choice Personality Inventory

Abstract: Research has shown that faking behavior affects the factor structure of single-stimulus (SS) personality measures. However, no published research has analyzed the effects of this phenomenon on the factor structure of forced-choice (FC) personality inventories. This study examines the effects of faking, induced in a laboratory setting, on the construct validity of a quasi-ipsative FC personality inventory based on the Five-Factor Model. It also examines the moderator effect of the type of experimental design (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 62 publications
0
16
0
2
Order By: Relevance
“…The findings have implications for the theory of faking at work. The psychometric theory of faking effects suggests that factor structure, construct validity, criterion validity, and incremental validity of personality inventories are negatively affected by faking (Salgado, 2016 ; Otero et al, 2020 ; Martínez et al, 2021a , b ). In connection with this, the findings of this meta-analytic study imply that other characteristics being equal, FC personality inventories would be more robust against the reduction of the validity levels than their counterpart SS personality inventories would be.…”
Section: Discussionmentioning
confidence: 99%
“…The findings have implications for the theory of faking at work. The psychometric theory of faking effects suggests that factor structure, construct validity, criterion validity, and incremental validity of personality inventories are negatively affected by faking (Salgado, 2016 ; Otero et al, 2020 ; Martínez et al, 2021a , b ). In connection with this, the findings of this meta-analytic study imply that other characteristics being equal, FC personality inventories would be more robust against the reduction of the validity levels than their counterpart SS personality inventories would be.…”
Section: Discussionmentioning
confidence: 99%
“…Otero et al [24] also reported evidence of the convergent-discriminant validity of the QI5F_tri using an SS personality inventory. Exploratory factor analyses confirmed the five-factor structure of the QI5F [25].…”
Section: Methodsmentioning
confidence: 58%
“…Hence, alternatives to SS personality inventories should be considered to reduce the impact of faking on the selection processes. In this sense, forced-choice (FC) inventories are instruments for assessing personality that better control the effects of faking [25,[53][54][55][56].…”
Section: Personality and Faking Behaviormentioning
confidence: 99%
See 2 more Smart Citations